'Leopards' under the pines: An account of continuity and change in the integration of forest land-uses in Landes de Gascogne, France. (December 2018) - Hautdidier, Baptiste; Banos, Vincent; Deuffic, Philippe; Sergent, Arnaud
Graphical abstract: Highlights: Storm damage in SW France has not led to an upheaval of the regional forest model. Large-scale threats to a regional forest cover can hinder evolutions of forest uses. Lack of change is due to efforts of operators on the upholding of a forest 'massif'. The 'massif' is simultaneously framed as cultivated, multifunctional and integrated. Emphasis on continuity has a leveraging role but obscures political imbalances. Abstract: The historical record of the definition of forest management and policy principles is a contentious one, characterized by tensions and conflicts between and among public authorities, private stakeholders and citizens. This paper is an empirical and analytical contribution to the understanding of the political and socio-economic factors influencing the integration of stakes in forest-dominated landscapes. Based on a case study of the 'Landes de Gascogne' forest region (southwestern France), it explores an apparent paradox that sees local landowners, following a massive storm damage, re-afforesting a Pinus pinaster plantation on a technical basis they know to be vulnerable. The authors highlight how, on which basis and by whom discourses and practices on forest integration have been sustained over decades in 'Landes', albeit being in fact reinvented on very different grounds—in a setting similar to the famous quote of the novel Il Gattopardo . The idea of a forest massif is identified as the object of most efforts, enabling the strategical use of three entwined perspectives: as a cultivated forest, a multifunctional land-use and an integrated chain. Ending with an analysis of the interplays of these dimensions, the paper further demonstrates the relevance of landscape and relational approaches to grasp the determinants of forest land-use conflicts.